APLIKASI PEMESANAN LAPANGAN OLAHRAGA THE CLUB BERBASIS SMS GATEWAY (Information Technology and Telematics, 2015)
Abstract- The booking  system is  running at The Club still usethe phone. Booking system that is currently running at The Clubstill uses the manual. Here  is  a description  of  the  process ofordering activity that  is  running on The Club is the  customercame  in  and ordered the  field  to play  sports, if  the  field isavailable,  the buyer make  a  payment and obtain proof  ofpayment, if  the  field diapakai then the buyer will have  to waituntil the field is available. System development methods in thisstudy is the SDLC phases requirements analysis, system designby using DFD, ERD and implementation of the system by usingPHP, and MySQL Gammu. Results of  this  research  isapplication-based sports  pitch reservations at The Club SMSGateway can  be  used to receive SMS booking and  reply toincoming  SMS automatically  in  accordance  with the  formatprescribed by the SMS The ClubKeywords – SMS Gateway, The Club, Gammu